The Influence of Service Quality, Destination Image, and Memorable Experience on Revisit Intention with Intervening Variables of Tourist Satisfaction - Edy Sahputra Sitepu; Rismawati Rismawati (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Abstract Purpose: This study aims to build a model for tourists' revisit intention who come to visit tourist destinations. Research methods: This study uses primary data with 400 samples assigned by random sampling. The data were processed using the Structural Equation Model (SEM). Results and discussions: In total (total effect) of each variable, which has the most considerable full effect, is given the destination image followed by service quality, tourist satisfaction, and memorable experience, respectively. For the mediation role, it is found that the tourist satisfaction variable is a mediator of the relationship between an unforgettable experience and revisit intention. Tourist satisfaction is not a mediator of the relationship between service quality and revisit intention and tourist satisfaction, nor is it a mediator of the relationship between destination image and revisit intention. Regarding revisit intention, the analysis results show that this variable is significantly influenced by the variables of service quality, destination image, and tourist satisfaction. Meanwhile, the effect of memorable experience is not statistically significant. Conclusion: The results of this study prove that efforts to increase tourists' revisit intention can be made by improving destination management that considers service quality, destination image, memorable experience, and tourist satisfaction.